Soil physico-hydraulic properties under organic conilon coffee intercropped with tree and fruit species - Souza, Gustavo Soares de; Alves, Danielle Inácio; Dan, Maurício Lima; Lima, Julião Soares de Souza; Fonseca, Abner Luiz Castelão Campos da; Araújo, João Batista Silva; Guimarães, Lorena Abdalla de Oliveira Prata (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the cultivation effects of organic conilon coffee (Coffea canephora) intercropped with tree and fruit species on soil physico-hydraulic properties. Conilon coffee managements in the organic system were: T1, full-sun monoculture; T2, T3, T4, and T5, intercropping with peach palm (Bactris gasipae), gliricidia (Gliricidia sepium), banana (Musa sp.), and inga (Inga edulis), respectively; and T6, an area of secondary native forest used as a control. The evaluated soil physico-hydraulic properties were: bulk density, porosity, plant-available water capacity, soil-penetration resistance, soil-water content, soil temperature, and least limiting water range. Conilon coffee intercropped with peach palm and gliricidia resulted in lower soil bulk density and penetration resistance, and in higher total porosity, microporosity, and soil-water content. Organic coffee shaded with peach palm and gliricidia improve the soil physico-hydraulic quality, in comparison with the soil under monoculture in full sun and with the soil of secondary native forest.